Penerapan Model Make A Match Berbantuan Media ICT Pada Pembelajaran Tematik Untuk Meningkatkan Prestasi Belajar Siswa SD - Try Nurhusni Setiati; Pebrian Tarmizi; Irfan Supriatna (JURIDIKDAS, 2023)
This study aims to improve the learning achievement of fourth grade students at SDN 133 Seluma in thematic learning by applying the Make a Match type cooperative model assisted by ICT media. This type of research was Classroom Action Research (CAR). The subjects in this study were teachers and fourth grade students (17 boys and 16 girls) at SDN 133 Seluma. Student achievement data in this study used the average formula and the percentage of learning completeness. The results of student achievement in thematic learning cycle I for SBdP subjects the average grade of 69.24 with classical learning completeness 60.60% experienced a very good increase in cycle II with an average value of 82.12 and classical learning completeness 87 ,87%. Meanwhile, in the first cycle of Indonesian language subjects with an average score of 63.63 and classical learning completeness 57.57%, there was an increase in the second cycle with an average value of 80.39 and 81.81% learning completeness. Thus, it can be concluded that the application of the Make a Match cooperative learning model assisted by ICT media can improve student achievement in class IV SDN 133 Seluma in thematic learning.